Intangibles in the world of transfer pricing : identifying - valuing - implementing - Heidecke, Björn; Hübscher, Marc C.; Schmidtke, Richard; Schmitt, Martin (Springer, 2021)
Intangible assets are becoming increasingly important as value drivers for multinational companies. It is a strategic question how to allocate intangibles within the multinational corporation. It needs to be defined by whom and under which conditions they can be utilized. Typical IP migration models such as licensing, joint development and transferring are becoming a focal point within tax audits across the globe. Hence,defining an intangibles system that fulfils the tax requirements is of utmost strategic importance for multinational corporations. A central question is how to value intangibles in line with the arm's length principle as is required internationally for transfer pricing purposes. Edited by leading transfer pricing and valuation experts in Europe, this comprehensive book offers practitioners an effective road map for identifying, valuing and implementing intangibles for transfer pricing purposes under consideration of both the OECD and local perspectives. It is therefore a must-have book for transfer pricing and valuation practitioners on all levels of experience. The book starts with an introduction to the role of intangibles in the world of transfer pricing including typical intangibles migration models. It describes common intangible assets across all types of industries, including e.g. automotive, consumer goods and software.Using several numerical examples, the book then covers state-of-the-art valuation methods including how to apply these methods in practice in a way consistent with the OECD Transfer Pricing Guidelines. The different country chapters written by local experts provide country-specific guidance on the legal framework concerning intangible assets from a transfer pricing and valuation perspective. Finally, the book covers practical advice on the implementation of an intangible assets system. This book offers invaluable guidance to practitioners seeking tools to apply the arm's length principle in the world of intangibles.